1951
DOI: 10.1103/physrev.82.278
|View full text |Cite
|
Sign up to set email alerts
|

Electron Density and Light Intensity Decay in Cesium Afterglows

Abstract: nucleus by observing the angular correlation of the emitted particles as a function of time. 2 One would expect a correlation to persist to times of the order of the total spin relaxation time T 2 of the intermediate nuclei j in the sample, perhaps milliseconds or better. 8 We show here how the theoretical delayed coincidence correlation function describing the effect of the magnetic field is to be obtained from the usual correlation function.The equations of the Weisskopf-Wigner treatment of the decay 4 can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1955
1955
2002
2002

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…From the results presented in figures 11 and 13 it can be seen that the loss rate is characteristic of a recombination process involving two charged particles, that the magnitude of the coefficient (10-7-10-6 cm3 s-1) is in approximate agreement with the values obtained by Dandurand and Holt (1951) and that there is a dependence of recombination coefficient on pressure. All these factors are consistent with dissociative recombination having been the principal loss mechanism.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…From the results presented in figures 11 and 13 it can be seen that the loss rate is characteristic of a recombination process involving two charged particles, that the magnitude of the coefficient (10-7-10-6 cm3 s-1) is in approximate agreement with the values obtained by Dandurand and Holt (1951) and that there is a dependence of recombination coefficient on pressure. All these factors are consistent with dissociative recombination having been the principal loss mechanism.…”
Section: Discussionsupporting
confidence: 67%
“…The results of these workers together with the atomic beam measurements of Hammer and Aubrey (1966) all indicate values in the range 10-9-10-11 cm3 s-l, in reasonable agreement with the values predicted by the collisional radiative model and of the twoelectron three-body process. On the other hand, the measurements by Dandurand and Holt (1951), at a pressure of about 1 torr using a cavity technique, gave large values of about 10-7 cm3 s-1. Loeb (1960) has pointed out that their suggested recombination mechanism, C S Z ~ + e+Csz + h v is unsatisfactory and has indicated that the large value of the recombination coefficient is indicative of a dissociative recombination process of the form CSZ+ + e+Cs~*+Cs + Cs.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The rate constant for cesium ion recombination has been measured by various investigators at pressures from 10"3 to I mm Hg (6,7,8);…”
Section: Analysis Of Czsium Nitrate-aluminum System During Nozzlmentioning
confidence: 99%
“…One experiment which is of interest in this work is the measurement of electron-ion recombination coefficients in caesium. This has been carried out by two observers, Mohler (1937) and Dandurand and Holt (1951).…”
Section: Wiroductionmentioning
confidence: 99%